Kontribusi dan Minat Generasi Milenial Terhadap Pekerjaan di Sektor Pertanian di Kabupaten Ciamis - Puspitasari, Anisa; Rachmawati, Jeti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The agricultural sector is one of the main contributors to employment absorption. However, there has been a noticeable decline in the number of millennial workers entering this sector. Millennials tend to have a negative perception of agriculture, viewing it as a less prestigious profession and one that offers limited financial rewards. This negative perception has led to the belief that the agricultural sector lacks both status and profitability. This study aims to: (1) Identify interest in agricultural sector employment in Ciamis Regency,(2) Observe employment trends among millennials in the agricultural sector, (3) Analyze the influence and contribution of millennials’ perspectives on agriculture in Ciamis Regency, and (4) Propose alternatives, solutions, and strategies to attract millennials to work in the agricultural sector. The trendline forecast results yielded the equation Y = 1E+06x - 2E+09, indicating a potential increase in youth employment in agriculture, though the growth is not expected to be significant.The findings show that interest among young people is categorized as very high. This suggests that millennials in Ciamis Regency are beginning to realize that being a farmer is neither as difficult nor as unattractive as they may have previously thought. Despite limitations in land and capital, the growing availability and application of innovations and modern technologies are making agricultural work more accessible and appealing.The study also indicates that the influence on interest, contribution, and employment in the agricultural sector in Ciamis Regency has been positive. What remains necessary is continuous guidance, both in terms of knowledge and technical skills, to help millennials sustain their agricultural ventures, implement innovative and technology-driven approaches, and identify profitable market opportunities.